What is the Level of Empathy in Medical Students of University of Ghana Medical School in Accra Ghana? - Lawson, Henry (International Journal of Global Health, 2020)
Empathy has been described as a multi-dimensional construct with cognitive and emotional components, both of which are concerned about responsivity to others. It has been touted as a skill essential for medical practice and thus useful to all healthcare professionals. It has been assessed in several countries and among several healthcare cadres however, there is a yawning gap in Ghana about its level in medical students. This study utilised a cross-sectional design to assess empathy using the ﻿Multi-Dimensional Emotional Empathy Scale in medical students of the University in Ghana. The scale has an alpha reliability of 0.88. One hundred and eleven students, aged 24 years ±1.5 years completed the study. Overall, there were more males than females. The mean empathy score for the cohort was 101SD 13 and this was adjudged to be low. There was no statistical difference between age, gender and clinical year and empathy in this cohort. The authors recommend that empathy, especially its cognitive aspects, should be taught in medical school curriculum of the University of Ghana Medical School, Accra.
Keywords: Empathy; medical practice; cognitive aspects.